Classe Média Brasileira: Afetos do Conservadorismo - um estudo a partir de "Tudo Bem" (Arnaldo Jabor, 1978) - Fernandes, Gabriel Marques (2022)
This dissertation has as a premise to investigate, historically, the Brazilian middle class from the study of the fictional resources of Tudo Bem (Arnaldo Jabor, 1978). The film, dialoguing with the effects of the decomposition of the Economic “Miracle” in the Ernesto Geisel Government, during the political opening, after the World Oil Crisis (1973-1979), builds a psychosocial narrative, presenting the situation of the Juarez, patriarch of the Cheap Family, who, stunned by his financial problems, happens to be haunted by the Ghosts of an Integralist, an Industrialist and a Poet, making him authorize the start of the renovation in his dining room, engaged by his wife, Elvira, wearing out the relationship between the workers in the microcosm of his apartment, leading that middle class to leave their nationalism, support for the Civil-Military Dictatorship, aside and reconcile with the multinational, Bill Thompson, possible future fiancé of Vera Lucia and boss of Zé Roberto, children of the couple. The question is: what is the form and cause of the behavior of the middle class in this theme/object? To solve the objective and problem of this research, of Reception was used as a theoretical-methodological tool in an interconnection between History, Cinema and Social Psychology. It was concluded that part of the middle class has a conservative behavior gestated by the affections of Anguish, Guilt and Fear from a psychic apparatus affected by the neurotic character regularized by a project of Catholic, Capitalist and Colonial country.